2014
DOI: 10.1111/1460-6984.12082
|View full text |Cite
|
Sign up to set email alerts
|

How much exposure to English is necessary for a bilingual toddler to perform like a monolingual peer in language tests?

Abstract: Typically developing 2;6-year-olds who are bilingual in English and an additional language and who hear English 60% of the time or more, perform equivalently to their typically developing monolingual peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 59 publications
11
118
1
3
Order By: Relevance
“…Numerous comparative studies between bilingual and monolingual first language learners have pointed to both similarities and differences in these aspects of word learning (see Bialystock et al, 2009). For example, past research has found that bilinguals and monolinguals appear to learn words for concepts at approximately the same rate (De Houwer, Bornstein, & Putnick, 2013;Hoff et al, 2012; see also Cattani et al, 2014). Bilinguals and monolinguals also show similar capacities for mapping words to objects in the learning environment (Byers-Heinlein & Werker, 2013;Werker, Byers-Heinlein, & Fennell, 2009) and appear to learn their first words at approximately the same time (Vihman, Thierry, Lum, Keren-Portnoy, & Martin, 2007).…”
Section: Cross-language Interactionmentioning
confidence: 90%
“…Numerous comparative studies between bilingual and monolingual first language learners have pointed to both similarities and differences in these aspects of word learning (see Bialystock et al, 2009). For example, past research has found that bilinguals and monolinguals appear to learn words for concepts at approximately the same rate (De Houwer, Bornstein, & Putnick, 2013;Hoff et al, 2012; see also Cattani et al, 2014). Bilinguals and monolinguals also show similar capacities for mapping words to objects in the learning environment (Byers-Heinlein & Werker, 2013;Werker, Byers-Heinlein, & Fennell, 2009) and appear to learn their first words at approximately the same time (Vihman, Thierry, Lum, Keren-Portnoy, & Martin, 2007).…”
Section: Cross-language Interactionmentioning
confidence: 90%
“…However, subsequent studies have not replicated this finding, even in samples with comparably high socioeconomic status (SES) (Hoff et al 2012), suggesting that there can indeed be differences in vocabulary sizes between monolinguals and bilinguals even with all else being equal. Interestingly, Cattani et al (2014) noted that a child needs to hear the dominant language at least 60% of the time to achieve vocabulary scores on par with those of his/her monolingual peers.…”
Section: Vocabulary Development In Bilingualsmentioning
confidence: 99%
“…For this reason, we have based most of our analysis below on TCV scores. In order to reduce the effect of the differences in the total number of concepts on each of the language adaptations, we first converted the raw TCV scores to a percentage of the maximum TCV score possible for each language pair (as carried out by Cattani et al 2014), and then converted these scores into z-scores, so that we could compare across groups. z-scores were calculated by subtracting the mean value of the %TCV on the CDI for the whole group of children from the individual scores, and then dividing this difference by the group standard deviation.…”
Section: Vocabulary Scoresmentioning
confidence: 99%
“…Sophie's exposure shifted towards more English (65%) from 3;4 as she started attending pre-school. Throughout most of the data collection, the two children had a fairly balanced (40%<X<60%) exposure to their two languages (Cattani et al, 2014). Overall, Sophie appears to be a fairly balanced child with a slight dominance in English while Anne who receives comparable exposure to English and French displays a much stronger preference for English in her own language use.…”
Section: Establishing Language Dominancementioning
confidence: 97%
“…Language exposure Cattani, Abbot-Smith, Farag, Krott, Arreckx, Dennis, & Foccia (2014) parental questionnaire was used to document the children's language exposure and use within their familial and social environments. Exposure to English was estimated to be around 55% for Anne, and around 58% for Sophie between the ages of 2;6 and 3;3.…”
Section: Establishing Language Dominancementioning
confidence: 99%